Application of Multimedia Technologies in Teaching Physics When Training Specialists in the Direction of Physics of Pedagogical Institutions - A.A. Ismailov (Global Scientific Publishing, 2022)
The use of multimedia technologies in teaching physics opens up new opportunities for the teacher, as well as develops the potential of students. Thanks to multimedia teaching tools, a new information environment is being created that combines modern methods and an approach to the study of physics
Keywords: physics; education; multimedia technologies; computer programs